2020
DOI: 10.3389/fpsyt.2020.00824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Psychological Impacts Related to COVID-19 of Vietnamese People Under the First Nationwide Partial Lockdown in Vietnam

Abstract: This is the first time in Vietnam that people have undergone “social distancing” to minimize the spreading of infectious disease, COVID-19. These deliberate preemptive strategies may have profound impacts on the mental health of the population. Therefore, this study aimed to identify the psychological impacts of COVID-19 on Vietnamese people and associated factors. We conducted a cross-sectional study during a one-week social distancing and isolation from April 7 to 14, 2020, in Vietnam. A snowball sampling te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 45 publications
7
81
2
2
Order By: Relevance
“…In this study, females were found to be more likely to suffer higher psychological stress. This result was consistent with the previous study, which also found that female may be associated with the worse psychological status during COVID-19 epidemic [24,25].…”
Section: Plos Onesupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, females were found to be more likely to suffer higher psychological stress. This result was consistent with the previous study, which also found that female may be associated with the worse psychological status during COVID-19 epidemic [24,25].…”
Section: Plos Onesupporting
confidence: 94%
“…Women may be more likely to have sleep problem, depressive symptom [26], and more intrusive flashbacks as they were more sensitivity to emotional stimuli and resulted in altered immune function and hormone level [25,27]. We also found that unmarried respondents were more likely to suffer higher pressure.…”
Section: Plos Onementioning
confidence: 56%
“…That female's stress was greater than that of males was also consistent with existing evidence [14,16] and similar studies conducted during the pandemic of COVID-19 from different countries [22][23][24][25]. The nding correspondents to epidimeological research suggesting that females have a higher risk of psychological outcomes [35].…”
Section: Discussionsupporting
confidence: 86%
“…Sex differences in self-reported stress are further re ected in the perceived need of psychological support services, which are often most evident in females. The sex differences of stress should be paid attention, and the government should provide appropriated paychological support services to improve female's resilience and alleviate their distress [23].…”
Section: Discussionmentioning
confidence: 99%
“…Validated versions of the tests in the various languages spoken in the seven countries were employed. Moreover, considering previous researches performed on a one-country level, IES-R and DASS-21 were used during COVID-19 research in China ( Hao et al., 2020 ), India ( Chew et al., 2020 ), Vietnam ( Le et al., 2020 ), Singapore ( Tan et al., 2020 ), and Philippines ( Tee et al., 2020 ); MASS was adopted in Italy ( Conversano et al., 2020 ; Baiano et al., 2020 ) and Brazil (Kozasa et al., 2020); PSS10 was used in Brazil (Kozasa et al., 2020), China ( Duan et al., 2020 ; Yan et al., 2020 ) and Colombia ( Pedrozo-Pupo et al., 2020 ); PHQ9 was employed in Greece ( Skapinakis et al., 2020 ), Italy ( Rapisarda et al., 2020 ), Spain ( Garre-Olmo et al., 2021 ) and China ( Yao, 2020 ); Brief-COPE was used in Australia ( Gurvich et al., 2020 ), Greece ( Skapinakis et al., 2020 ), United Kingdom ( Dawson and Golijani-Moghaddam, 2020 ) and USA ( Umucu and Lee, 2020 ).…”
Section: Methodsmentioning
confidence: 99%